2005
DOI: 10.1016/j.bbamcr.2004.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria are intracellular magnesium stores: investigation by simultaneous fluorescent imagings in PC12 cells

Abstract: To determine the nature of intracellular Mg2+ stores and Mg2+ release mechanisms in differentiated PC12 cells, Mg2+ and Ca2+ mobilizations were measured simultaneously in living cells with KMG-104, a fluorescent Mg2+ indicator, and fura-2, respectively. Treatment with the mitochondrial uncoupler, carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (FCCP), increased both the intracellular Mg2+ concentration ([Mg2+]i) and the [Ca2+]i in these cells. Possible candidates as intracellular Mg2+ stores under these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 62 publications
10
107
0
1
Order By: Relevance
“…In the study showing inhibition of lyase activity in hOGG1, Mg 2ϩ concentrations of 5 mmol/l were required for this effect. However, it has recently been shown that the concentration of Mg 2ϩ in mitochondria is ϳ1.2 mmol/l, and much of this Mg 2ϩ is bound to ATP (44). Therefore, it is unlikely that Mg 2ϩ concentrations in mitochondria will adversely affect hOGG1 lyase activity.…”
Section: Hogg1 Protects From Ffa-induced Apoptosismentioning
confidence: 99%
“…In the study showing inhibition of lyase activity in hOGG1, Mg 2ϩ concentrations of 5 mmol/l were required for this effect. However, it has recently been shown that the concentration of Mg 2ϩ in mitochondria is ϳ1.2 mmol/l, and much of this Mg 2ϩ is bound to ATP (44). Therefore, it is unlikely that Mg 2ϩ concentrations in mitochondria will adversely affect hOGG1 lyase activity.…”
Section: Hogg1 Protects From Ffa-induced Apoptosismentioning
confidence: 99%
“…Thus in cells, where the average potassium 118 Chapter 7. Conclusion ion concentration is about 140 mM [192] and the average magnesium concentration ranges from 0.05 to 1 mM [193,194], we can expect the head and tail domains to have a radius of 3 nm or larger. Furthermore, the concentration of ions in cells can have locally higher values thus leading to more accumulation in the head and tail domains and a greater effect on keratin filaments, bundles and networks.…”
Section: Resultsmentioning
confidence: 99%
“…They also correspond to the intracellular concentrations of 140 mM for potassium ions [192]. And in the case of magnesium ions, the intracellular concentration depends on the cell type and ranges from 0.05 to 1 mM [193,194].…”
Section: Measurements On Keratin Bundlesmentioning
confidence: 99%
“…Magnesium play an important role in ATP formation in the mitochondria with ATP critical to Aβ misofolding and APP and Aβ involved in ATP generation in the mitochondria [89]- [92]. Magnesium imbalance in cells are associated with mitochondrial apoptosis [93] and Aβ oligomer formation with defective energy metabolism that indicate induction of NAFLD and obesity in global populations [3] [39] [40].…”
Section: Magnesium Therapy Regulates Amyloid Beta Metabolism With Impmentioning
confidence: 99%